Analysis of adverse drug reactions in remdesivir therapy using the Naranjo Algorithm - Afifah Fauziyyah; Rani Sauriasari; Ratika Rahmasari; Hindun Wilda Risni; Puji Astuti (PT WIM Solusi Prima, 2026)
Research on the safety of remdesivir in Indonesian subjects for COVID-19 therapy is still limited and has yielded different results. None of these studies have used the Naranjo algorithm to analyze the causality of remdesivir safety. This study aimed to evaluate the safety of remdesivir in patients with severe COVID-19. Data were collected using medical records of patients with severe COVID-19 at Cengkareng Regional Hospital, Indonesia. The study was conducted retrospectively with a cohort study design. Subjects consisted of the remdesivir group (n=80) and the non-remdesivir group (n=80). Adverse drug reactions (ADRs) were observed, and causality analysis of ADRs was performed using the Naranjo algorithm. The study found 10 ADRs experienced by patients during treatment. ADRs were more common in the remdesivir group than in the non-remdesivir group (58.8% vs 53.8%; p=0.633). Significant events with a high proportion in the remdesivir group were increased ALT (p=0.037) and lymphopenia (p=0.01). Hepatotoxic reactions associated with remdesivir use were associated with P-glycoprotein (P-gp) inhibitor interactions. Decreased lymphocyte counts were closely related to the clinical condition of the study subjects, namely patients with severe COVID-19, and this condition was associated with a poor prognosis. Increased blood triglycerides, lymphopenia, and decreased estimated glomerular filtration rate (eGFR) were categorized as probable. Meanwhile, nausea, melena, QT interval prolongation, increased ALT, increased AST, hyperuricemia, and neutrophilia were categorized as quite possible. The results of this study can be concluded that remdesivir causes liver dysfunction manifested by increased ALT values ​​and decreased lymphocyte counts, which worsen the condition of patients with severe COVID-19.